ZISWAF in Neighboring Countries: History, Characteristics, and Management Problems in Malaysia and Singapore - Wahyu Ramadhani; Widia Sari; Aidil Alfin (ICIEFS Proceeding, 2025)
This study examines the history, characteristics, and challenges of Zakat, Infaq, Sedekah, and Waqf (ZISWAF) management in Malaysia and Singapore, two distinct models of Islamic social fund management in Southeast Asia. The primary objective of this study is to understand how the social, political, and legal systems in both countries influence the effectiveness and efficiency of ZISWAF management. This study employed a library research method with a qualitative descriptive approach through analysis of scientific literature and applicable institutional regulations. The results show that Malaysia implements a decentralized system involving the State Islamic Religious Council (MAIN) in each state, which autonomously manages zakat and waqf. This model allows for local flexibility but faces challenges such as regulatory differences, interregional coordination, and variations in the effectiveness of fund distribution. In contrast, Singapore adopts a centralized system under the Majlis Ugama Islam Singapura (MUIS), which operates under the Administration of Muslim Law Act (AMLA). This system stands out for its professionalism, transparency, and digitalization, despite facing the constraint of a limited number of beneficiaries due to high socio-economic conditions. Both countries have demonstrated progress in modernizing ZISWAF management through the implementation of corporate governance and the use of digital technology. In conclusion, Malaysia excels in institutional innovation and the diversity of regional approaches, while Singapore serves as a model for efficient, transparent, and adaptive ZISWAF governance to modern economic developments. This study contributes to strengthening sustainable ZISWAF management models at the regional and global levels.